Remarkable response to PD-1 inhibitor in a patient with extensive-stage small cell lung cancer: a case report and literature review - Yuan, Ge; Liu, Xiangliang; Zhang, Xinwei; Song, Wei; Lu, Jin; Ding, Zhongyang; Chen, Xiao (Frontiers in Immunology, 2023)
We report a case of a 59-year-old male diagnosed with extensive-stage small cell lung cancer (SCLC). He received first-line platinum doublet chemotherapy and second-line topotecan-based regimen, but experienced disease progression after each line of therapy. He was then treated with Sintilimab, a PD-1 inhibitor, in combination with nab-paclitaxel in the third-line setting, which resulted in significant tumor shrinkage. Restaging scans showed a partial response per RECIST criteria with 62% reduction in tumor burden. This case highlights the application and efficacy of immune checkpoint inhibitors in extensive-stage SCLC.